The value of WeChat application in chronic diseases management in China. (November 2020) - Chen, Xin; Zhou, Xi; Li, Huan; Li, Jinlan; Jiang, Hua
Highlights: What is already known about the topic? The prevalence of chronic diseases has increased rapidly in recent decades. There is still no unified measure for chronic diseases management in China. WeChat has been widely used in China. It may be an effective tool for managing chronic disease. Many researchers have reported the effectiveness of WeChat in chronic diseases management. But few studies discussed the value of WeChat in chronic diseases management and analyzed the potential reasons. What this paper adds? Based on the status of WeChat application in chronic diseases management and the characteristics of WeChat technology, this paper discusses the advantages and limitations of previous studies, and proposes feasible solutions to provide reference value for further studies. Implications for practice, theory or policy This review may provide idea for medical institution and government in chronic diseases management. Abstract: The prevalence of chronic diseases in China has increased rapidly in recent decades. Although the management rate of chronic diseases has improved, there is still no unified and effective management measure for chronic diseases at present. This highlights the importance of effectively managing chronic diseases. With the development of e-health, the ways of getting medical consultation have changed. WeChat is an extremely popular social application in China. It is easy to operate and can offer multiple functions. Many researches have reported the effectiveness of WeChat in chronic diseases management. Based on the status of WeChat application in chronic diseases management and the characteristics of WeChat technology, we firstly focused on the WeChat application on the management of chronic diseases such as hypertension, diabetes, coronary heart disease and cancer. Then we discussed the value of WeChat in chronic diseases management and analyzed the potential reasons. Lastly, we discussed the limitations of present researches. WeChat can be an effective tool for the management of chronic diseases, but the promotion of this mode needs support and efforts from various aspects to eventually realize improving public health.